Nilai-Nilai Pendidikan Karakter yang Terkandung dalam Nasehat Ritual Katoba pada Masyarakat Etnik Muna di Kabupaten Muna - La Aso . (Laboratorium Jurusan Antropologi, Fakultas Ilmu Budaya, Universitas Halu Oleo, 2017)
This study aims to describe and analyze the educational character values in katoba ritual advise on Muna ethnic Group Society at Muna regency. This research is qualitative. This research was conducted in several villages in Katobu sub-district of Muna Regency. The kind of data in this research is qualitative data. The data source consists of primary data and secondary data. The informants of the research were determined purposively. To gather information, both primary and secondary data, two techniques were used, namely observation, and in-depth interviews. Data analysis was done descriptively qualitative and interpretative. The results of this research showed that katoba ritualmeans repent and forswear to avoid any act having sin or bad action. Katoba ritual on Muna ethnic group society is the process for children, so it needs an advisor figure(lebe) to give advice and teaching the katoba participants. The advise involves 7 items, they are (1) do-soso ‘regreting’; (2) do-feka-kodohodhosa ‘avoiding the sin’; (3) do-tehikamokula moghane ‘obeying father’; (4) do-tehikamokula robhine ‘obeying mother’; (5) do-tehipoisaha ‘obeying older brothers/sisters’; (6) do-asiagho poaiha ‘loving younger brothers/sisters’; and (7) miina dae-ala haku naasi ‘not taking/eating people’s/goods/rights’. Katoba ritual is a local wisdom for Muna ethnic group in Muna Regency that has several educational characters meanings or values, and relevant to the pupose and function of character education, like teaching and improving the role of family to be participated in developing children’s attitude and potention. Keywords: katoba ritual, character education, Muna etnic group